Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas IV UPT SD Negeri Percobaan Medan Menggunakan Problem-based Learning pada Materi Luas Permukaan dan Volume Tabung - Muthmainnah, Putri; Hutabarat, Ester Julia Nurhayati; Hutagalung, Bella Aprillia; Rambe, Kartina Rahmadhani (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This study focuses on improving the mathematics learning achievement of fourth-grade students at UPT SD Negeri Percobaan Medan by implementing the Problem-Based Learning (PBL) method on the topic of surface area and volume of cylinders. The classroom action research conducted consisted of two cycles, each cycle involving planning, implementation, observation, and reflection stages. The planning stage included the preparation of Lesson Plans (RPP) and teaching aids and evaluation tools by the researcher and teacher. The implementation of the action involved active learning with students playing a role in solving real-world problems. Observations were made to monitor student and teacher activities during the learning process. The reflection stage was used to analyze the results of observations and evaluations to formulate the next cycle. The results of the study showed a significant increase in student understanding and participation. In the first cycle, 57.24% of students achieved the minimum learning completeness criteria, and this percentage increased in the second cycle. In addition, students showed an increase in critical, analytical, and collaborative thinking skills. The implementation of PBL not only improved learning outcomes but also built student motivation and interest in learning mathematics. Based on these findings, the research recommends the widespread implementation of the PBL method as an effort to improve the quality of mathematics learning.